أثر قانون هيئة أسواق المال الكويتي على الشركات المدرجة : دراسة تحليلية - عازمي، زيد مبارك زيد السمران (Ahmad Ibrahim Kulliyyah of Laws, International Islamic University Malaysia, 2021)
Stock exchanges are considered to be one of the foundations of the national economy in the State of Kuwait. This is evident since the establishment of the Kuwait Stock Exchange in the middle of the last century when the Law of Companies No. 15 of 1960 was issued, which was accompanied by development and prosperity in issuance of legislations to regulate the Kuwait Stock Exchange and to indicate the relationship among the State as an entity in one side and the companies, shareholders and investors in the other side. It has recently become an obstacle to the large number of legislations regulating this market. The State had to issue a legislation to regulate all relations between all the market participants and create one administration to manage this entire entity. The research is summarized in addressing the provisions of the Capital Market Authority Law No. 7/2010 amended by the Law 22/2015 in an analytical study of the law provisions and explaining its impact on the companies listed on the Kuwait Stock Exchange. In this research, the researcher used the analysis of the law texts indicating the deficiencies in them. The study covered all aspects of the Capital Markets Authority Law including; establishment of the Capital Markets Authority, its owner and its powers. It also covered all aspects of the Kuwait Stock Exchange from the Boursa Kuwait Company and the Kuwait Clearing Company in addition to the most important new rules that the law stipulated, which need to be studied, including listing rules, governance rules, acquisition rules and disclosure rules. The researcher concluded that the law has aspects of development, keeping pace and filling the deficiencies. On the other hand, it was an obstacle facing many companies. This led to a legal defect which included many provisions that need interpretation and clarification, and others that need amendment. The importance of the research lies in the novelty and bifurcation of the law. It covers all aspects of the listed companies from the date of establishing the company until the termination of the company by liquidation or integration.